2016
DOI: 10.1177/0263617415623426
|View full text |Cite
|
Sign up to set email alerts
|

The uptake of metal elements into poly(1-methylpyrrol-2-ylsquaraine) particles and a study of their porosity

Abstract: The article reports an experimental study of the metal uptake properties of poly(1-methylpyrrol-2-ylsquaraine) particles, in the context of 51 elemental metal complexes. Vagaries of the experimental results meant that the final analysis took place for 43 of these metals. After an initial descriptive analysis, an Analysis of Variance model was fitted. This revealed that several factors, some intrinsic to the metals themselves, others relating to the experimental conditions, have an important influence on the ad… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
7
0

Year Published

2018
2018
2020
2020

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(7 citation statements)
references
References 27 publications
0
7
0
Order By: Relevance
“…PMPS particles were prepared as previously described [18,19]. Equimolar quantities of squaric acid and 1-methylpyrrole in butanol were refluxed for 18 h (Figure 1).…”
Section: Pmps Particlesmentioning
confidence: 99%
See 1 more Smart Citation
“…PMPS particles were prepared as previously described [18,19]. Equimolar quantities of squaric acid and 1-methylpyrrole in butanol were refluxed for 18 h (Figure 1).…”
Section: Pmps Particlesmentioning
confidence: 99%
“…Poly (1-methylpyrrol-2-ylsquaraine) (or PMPS) was one of three types of new squaraine compounds that were first reported in 1965 by Triebs and Jacob [17], but its unique particle shape was not reported until 2005 [18]. Extensive elemental metal adsorption studies on PMPS particles, along with physical studies on their internal porous nature, were published in 2016 [19]. They have also been recently reported as humidity sensing materials by Xiao et al, 2018 [20].…”
Section: Introductionmentioning
confidence: 99%
“…In 2005, [1] the first electron microscope image of PMPS powder was published and showed that the polymer particles were uniformly spherical and approximately 1.3 μm in diameter. Subsequent studies have investigated both surface and internal morphologies of PMPS particles [19] as well as more detailed particle size distribution. [17] The spherical nature of PMPS particles, coupled with their thermal degradation, has been utilized in the preparation of hollow silica shells, [1,17,24] and their adsorption of metal compounds [19] has been further utilized to produce core-shell particles.…”
Section: Introductionmentioning
confidence: 99%
“…[12] The original synthesis of PMPS in the Triebs and Jacob paper [2] implied reflux of the two constituent reactants in ethanol, from which the precipitate was separated as a blue to blue-green insoluble polymer. Further reported syntheses using ethanol followed this, [3] but all syntheses from 1990 onwards were undertaken in butanol, [13][14][15][16][17][18][19][20][21] with one run under an inert atmosphere. [16] Squaraine compound syntheses are acidcatalyzed condensation reactions where the squaric acid is a strong enough acid to self-catalyze, although removal of the produced water, usually achieved through azeotropic distillation, is essential for such reactions to proceed.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation